1977
DOI: 10.1093/ageing/6.3.144
|View full text |Cite
|
Sign up to set email alerts
|

The Difficulties of Old People Taking Drugs

Abstract: There is considerable interest in the problems of the elderly taking drugs correctly and appropriately. A recent survey (Parkin et al. 1976) showed that these problems that have long been known in geriatric practice have now been noted by general physicians. This review was undertaken when an occupational therapist in a geriatric unit team noted that, although patients and their relatives were taught methods of dressing, toileting, shaving, bathing, eating, walking, transferring to a chair, wheelchair mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Many of the patients in our survey were in receipt of several different medications, and this may have contributed to their much poorer compliance. Most patients cannot take more than three concurrent regular medications reliably (Ref 4).…”
Section: Tablet Taking By Type 2 Diabetics: Medication Errors and Poomentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the patients in our survey were in receipt of several different medications, and this may have contributed to their much poorer compliance. Most patients cannot take more than three concurrent regular medications reliably (Ref 4).…”
Section: Tablet Taking By Type 2 Diabetics: Medication Errors and Poomentioning
confidence: 99%
“…It is human nature for many patients to make potentially serious errors in the taking of prescribed medications ( Refs 1,2). Elderly patients are particularly at risk, because of forgetfulness and confusion (Refs 3,4). Doctors often fail to explain how and when to take tablets and multiple medications compound this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Various drug education and record cards which patients keep have also been designed (Atkinson et al 1977).…”
Section: Patient Education and Coordination Ofcarementioning
confidence: 99%
“…A number of surveys have shown that the elderly as a group are generally not aware of the implications of symptoms, or will attribute them to the effects of ageing. Mental deterioration, living alone, problems of mobility, social withdrawal and an inability to obtain help will increase the possibility of non-compliance, with adverse reactions and treatment failures developing undetected (Atkinson et al 1977, Barrowclough & Pegg 1982.…”
Section: Detecting Non-compliancementioning
confidence: 99%
See 1 more Smart Citation